2010
DOI: 10.1007/s00340-010-3941-x
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of the filament density of ultrashort intense laser pulses in air

Abstract: We experimentally and numerically characterize multiple filamentation of laser pulses with incident intensities of a few TW/cm 2 . Propagating 100 TW laser pulses over 42 m in air, we observe a new propagation regime where the filament density saturates. As also evidenced by numerical simulations in the same intensity range, the total number of filaments is governed by geometric constraints and mutual interactions among filaments rather than by the available power in the beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
3
34
0
1
Order By: Relevance
“…This has acquired a form of new research status for potentially utilizing ultrashort laser pulses for cloud seeding [1][2][3][4][5][6]. The observation of the phenomenon in various conditions by several groups is now well established, and some basic processes at play are identified [7][8][9][10][11][12][13][14]. The challenges that are being addressed in the current pre-proposal are as follows: a.…”
Section: Introductionmentioning
confidence: 99%
“…This has acquired a form of new research status for potentially utilizing ultrashort laser pulses for cloud seeding [1][2][3][4][5][6]. The observation of the phenomenon in various conditions by several groups is now well established, and some basic processes at play are identified [7][8][9][10][11][12][13][14]. The challenges that are being addressed in the current pre-proposal are as follows: a.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction is attractive if the filaments are in phase, and repulsive if they are in antiphase [27,28], corresponding to constructive and destructive interferences in the photon bath, respectively. Previous theoretical and experimental studies have shown that the relative phase between filaments is mainly randomly driven by intensity fluctuations during the collapse [29] and is then stabilized for the filaments propagating after the collapse [30].Recently we showed that at laser powers exceeding 100 TW, this mutual interaction limits the density of filaments in the transverse beam profile [31], resulting in the * corresponding author jean-pierre.wolf@unige.ch rise of the photon bath intensity. As a consequence, the photon bath effectively contributes to non-linear effects like white-light generation [32] or laser-induced condensation [33], resulting in an overall increase of the yield of these processes.…”
mentioning
confidence: 95%
“…Recently we showed that at laser powers exceeding 100 TW, this mutual interaction limits the density of filaments in the transverse beam profile [31], resulting in the * corresponding author jean-pierre.wolf@unige.ch rise of the photon bath intensity. As a consequence, the photon bath effectively contributes to non-linear effects like white-light generation [32] or laser-induced condensation [33], resulting in an overall increase of the yield of these processes.…”
mentioning
confidence: 99%
“…19 From this location, the filamenting beam propagated through an open diffusion chamber (110 Â 40 Â 40 cm inner dimensions) 20 filled with ambient air. The temperature and RH in the chamber were controlled by a heated water reservoir at its top, and a fluid circulator at a temperature of À15 C on its bottom.…”
mentioning
confidence: 99%
“…21,22 However, above $500 GW/cm 2 , the effect of the laser increases faster than linearly while the filament number saturates due to spatial constraints. 19 These diverging behaviours evidence a substantial contribution from the photon bath in the highintensity regime. Such contribution of the photon bath to a non-linear process at extreme average incident intensity has indeed been observed in the case of white-light generation.…”
mentioning
confidence: 99%